Gelatin binding to the 8F19F1 module pair of human fibronectin requires site-specific N-glycosylation. - Millard, C; Campbell, I; Pickford, A (2005)
The gelatin (denatured collagen) binding domain of the extracellular matrix protein fibronectin contains three potential N-glycosylation sites. Complete deglycosylation of this domain is known to reduce the thermal stability of the eighth type 1 (8F1) module. We have conducted a site-specific analysis of the structural and functional consequences of N-linked glycosylation in the 8F19F1 module pair. Three glycoforms have been identified by mass spectrometry and nuclear magnetic resonance spectroscopy. Chemical shift differences between the glycoforms have revealed an intimate interaction between one N-linked sugar and the polypeptide that is critical for gelatin binding, as shown by affinity chromatography.